Use of Wickerhamomyces anomalus Strains from Biologically Aged Wines to Improve the Sensorial Profile of Young White Wines - Juan Carbonero-Pacheco; Álvaro García-Jiménez; Juan Carlos García-García; Inés M. Santos-Dueñas; Teresa García-Martínez; Juan Moreno; Jaime Moreno-García; Juan Carlos Mauricio (Applied Sciences)
Non-Saccharomyces yeasts play a significant role in winemaking, offering unique benefits and contributing to wine complexity and varied and desirable aromatic profiles. This work focuses on the sensory improvement of Pedro Ximénez white wines using selected strains of Wickerhamomyces anomalus isolated from biologically aged wines. Chemical and microbiological analyses confirmed the implantation of W. anomalus; these yeast strains appear to displace indigenous non-Saccharomyces species in the must and produce large amounts of ethyl acetate and lower ethanol content. Wines made with W. anomalus strains were judged negatively by the tasting panel due to a nail polish/varnish odor and a strong, bitter taste; however, when these wines were blended with wine normally produced by spontaneous fermentation, the judges rated them positively, highlighting fruity aromas not detected under other conditions. These results conclude that W. anomalus strains isolated from biologically aged wines could be useful for modulating the sensory profile of white wines. Moreover, their use in combination with other yeasts or in immobilized form could improve the results obtained and avoid the blending process. The high yield of ethyl acetate produced by these strains could be of interest as an alternative to current methods of producing this compound, including the use of these wines for the production of quality vinegar.